The trickster figures in Thomas King and Tomson Highway - Machová, Klára (2006)
The thesis deals with the problem of a trickster figure as it is seen in current scholarly debate - generality or diversity of this figure, trickster or culture hero features. Then it specifies trickster features as they are seen at mythological characters focused on North American Indian. In the second part of the thesis, it offers an analysis of Thomas King's novel MEDICINE RIVER, and Tomson Highway's plays THE REZ SISTERS and DRY LIPS OUGHTA MOVE TO KAPUSKASING in relation to trickster figures used there.